The Effectiveness of Campaign Digital Politics in Increasing the Electability of Prospective Candidates: A Analysis General Election of President and Vice President 2019 - Hidayat, Arif; Rahayu, Lilik Puja; Utami, Cahyaning Bhakti; Anggraini, Ine; Subandi, Yeyen (PT Inovasi Pratama Internasional, 2024)
In this digital era, political campaigns have experienced significant changes with the emergence of various social media platforms and digital technology. This phenomenon is no exception in the context of the 2019 presidential and vice-presidential general elections in Indonesia. Digital political campaigns have become an integral part of candidates' strategies in winning the hearts of voters and increasing their electability. In this analysis, we evaluate the effectiveness of digital political campaigns in increasing the electability of prospective candidates in the 2019 presidential and vice-presidential general elections. We identify the strategies and tactics used by candidates and their campaign teams in utilizing digital technology to achieve their political goals, as well as the impact digital political campaigns on public perception and the final results of the general election. Using qualitative analysis methods, we collect data from various social media platforms and apply content analysis to understand the influence of digital political campaigns. The research results show that digital political campaigns have a significant impact in increasing the electability of prospective candidates, by increasing visibility, recognition and interaction with voters through social media. In addition, we also discuss other factors that influence election outcomes, such as the participation of young voters, the potential for polarization, and the influence of dynastic politics. Thus, this analysis provides in-depth insight into the role of digital technology in contemporary politics and its implications for democracy and the general election process in Indonesia.